Economic welfare between positive economy endoscopy and the principles of Islamic economics - Hamed, Alemam (Finance and Business Economies Review, 2019)
Economic welfare economic situation is characterized by the individual and the group; they differ in terms of the application of the economic system to another economic system, so we find that the individual or society (ie states) seeks to achieve the greatest live happy to members of the necessities of goods and services. If the economic well-being is the product of a social dealt with economic theory through the availability of the national income; the economic well-being of the Islamic economy, is the product of an individual he believed to enjoy the life of the world through the availability of disposable income even though he knows that life is not a minimum Dar decision but the other life when Muslim individual is to achieve real economic well-being.